1999
DOI: 10.1111/j.1558-5646.1999.tb05380.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Speciation in Sticklebacks: Environment-Dependent Hybrid Fitness

Abstract: Abstract.-"Ecological" speciation occurs when reproductive isolation evolves as a consequence of divergent selection between populations exploiting different resources or environments. We tested this hypothesis of speciation in a young stickleback species pair by measuring the direct contribution of ecological selection pressures to hybrid fitness. The two species (limnetic and benthic) are strongly differentiated morphologically and ecologically, whereas hybrids are intermediate. Fitness of hybrids is high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
395
6
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 355 publications
(415 citation statements)
references
References 43 publications
13
395
6
1
Order By: Relevance
“…1f). This pattern corroborates the results from transplant experiments in the native lake showing a growth disadvantage in intermediate hybrids, relative to the two parental species in their native habitats 14,21,22 . Thus, our results on the genetics of divergence in niche use and whole-organism performance suggest that the underlying genetic basis of extrinsic postzygotic reproductive isolation between benthic and limnetic stickleback is largely additive.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…1f). This pattern corroborates the results from transplant experiments in the native lake showing a growth disadvantage in intermediate hybrids, relative to the two parental species in their native habitats 14,21,22 . Thus, our results on the genetics of divergence in niche use and whole-organism performance suggest that the underlying genetic basis of extrinsic postzygotic reproductive isolation between benthic and limnetic stickleback is largely additive.…”
Section: Discussionsupporting
confidence: 88%
“…Each species pair likely arose from a double lake invasion via the sea 12 , followed by further divergence with gene flow 16,20 . Hybrids are intermediate in morphology and are outperformed by each parental species in the preferred parental habitats 14,21-23 . Little intrinsic postzygotic isolation has evolved between the species, as laboratory-reared hybrids are viable and fertile 16,21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of hybrid zones have suggested that phenotypically intermediate hybrid individuals often perform poorly in parental niches (e.g., Hatfield and Schluter 1999; Godoy-Herrera et al. 2005), and DeLacy and Morton (1943) indicated that the two species have very different habitat use and migratory life history in sympatry (see above).…”
Section: Discussionmentioning
confidence: 99%
“…These species are morphologically adapted to their contrasting food sources: benthic stickleback primarily feed on invertebrates inhabiting the substrate or attached to vegetation, whereas limnetics specialize on zooplankton [1012]. Although hybrids exist in the wild [1315] and there are no strong intrinsic incompatibilities [14,16], benthics and limnetics show nearly complete assortative mating in experimental trials [17]. Previous no-choice mating trials suggested that benthic and limnetic females prefer mates with similar body size [1820] and shape [20].…”
Section: Resultsmentioning
confidence: 99%